2019
DOI: 10.1167/iovs.18-26051
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Effect of the Unilateral Corneal Nerve Cut on Both Ocular Surface and Lacrimal Gland

Abstract: PURPOSE. This study investigated the effect of a unilateral cut of the corneal nerve on the bilateral ocular surface and tear secretory function. METHODS. Seven-week-old female BALB/c mice were divided into control and nerve-cutting (NC) groups (n ¼ 60). The left cornea was partially incised with a 2-mm circular trephine through the upper half of the stromal layer. Lissamine green corneal staining and tear volume measurements were conducted, and corneal whole-mount staining using class III b-tubulin antibody w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…There is also a wealth of evidence to show that contralateral structural and molecular changes can occur both in the periphery and the central nervous system in response to a unilateral insult (Koltzenburg et al, 1999;Shenker et al, 2003;Ferrari et al, 2014;Lee et al, 2019).…”
Section: Evidence That Corneal Nerve Abnormalities Shape the Central mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a wealth of evidence to show that contralateral structural and molecular changes can occur both in the periphery and the central nervous system in response to a unilateral insult (Koltzenburg et al, 1999;Shenker et al, 2003;Ferrari et al, 2014;Lee et al, 2019).…”
Section: Evidence That Corneal Nerve Abnormalities Shape the Central mentioning
confidence: 99%
“…For example, unilateral corneal damage induces inflammatory responses in contralateral mouse eyes (Yamaguchi et al, 2016;Lee et al, 2019), the TG (Ferrari et al, 2014), and the central nervous system (Launay et al, 2016). Indeed, FOS-like positive neurons were seen in the contralateral trigeminal brainstem after corneal nerve damage (Launay et al, 2016).…”
Section: Evidence That Corneal Nerve Abnormalities Shape the Central mentioning
confidence: 99%
“…For MG analysis, upper and lower samples of each eye were pooled (8W, n = 9; 1Y, n = 5; 2Y, n = 3). The proportion of IFN-γ and IL-17A in CD4 + and CD8 + T cells was assessed as a subset of effector T cells in the LGs and DLNs [48].…”
Section: Flow Cytometry For Immune Cells and Oxidatively Stressed Cellsmentioning
confidence: 99%
“…Previous studies have shown that unilateral corneal injury can produce bilateral effects on corneal innervation, immune cells, and cytokines 34 36 . For example, 14 days after unilateral trephine-induced corneal nerve injury, a contralateral reduction in stromal and sub-basal nerve innervation was found, along with bilateral ocular inflammation 36 . Corneal sensitivity in these studies, however, was not assessed.…”
Section: Discussionmentioning
confidence: 99%